Neoliberal Policies and Poverty: An Examination of the Impact of Fuel Subsidies Removal on Women in Nigeria - Philip Terzungwe Vande; Isah Abdulraman (Journal of Arts, Humanities and Social Science, 2025)
Neoliberal policies implemented by African nations have adversely affected the quality of life for citizens, especially women. The elimination of subsidies on petroleum products has resulted in a heightened cost of living in Nigeria, impacting transportation, food, and other consumer items, and exacerbating poverty rates. This study examined the effects of eliminating fuel subsidies on the livelihoods of women in Nigeria. A survey research design was adopted in this study, where data from the questionnaire, focus group discussions, and in-depth interviews were triangulated. Secondary data were also used to complement the primary data. The study embraced the dependency theory, providing a comprehensive analysis and framework on the nature and character of neoliberalism. It was established that the elimination of fuel subsidies has resulted in the increasing impoverishment of women in Nigeria and throughout Africa. The research demonstrated that several women have lost their livelihoods, particularly since various Small and Medium Enterprises (SMEs) managed by women have failed, impoverishing countless women and their dependents. The study concluded that neoliberalism has exacerbated social welfare difficulties, intensified poverty in certain regions, and enlarged disparities in pre-existing injustices. The abrupt elimination of subsidies has resulted in the impoverishment of citizens, with women experiencing particularly severe hardships. By this removal, the poor have been disproportionately affected by economic austerity measures and reduced government expenditure on social services. It was recommended, among others that inclusive development solutions should be prioritised by policymakers. Again, the government ought to fund transport services to alleviate the difficulties caused by rising prices of products and services resulting from increased fuel costs. The study also recommends that the Nigerian government should introspect and enact widely supported policies aimed at poverty alleviation.